Dementia and cognitive impairment in Parkinson's disease. Issue 12 (December 1988) - Girotti, F; Soliveri, P; Carella, F; Piccolo, I; Caffarra, P; Musicco, M; Caraceni, T
Abstract : The frequency of dementia, the clinical characteristics and the pattern of cognitive impairment were studied in 147 unselected Parkinsonian patients. Twenty-one patients (14.28%) were judged to be demented. They had a more severe and widespread cognitive deficit although they were affected particularly in those tests that already discriminated Parkinsonian patients from controls. A direct comparison of Parkinsonian dementia with other types of dementia is needed to validate the concept of subcortical dementia.